Congregation-Based Service Financing Scheme (LASISMA) in Improving Customer Business at BMT NU Larangan Pamekasan Branch - Hasanah, Fitriyatun; Asy’ari, Qaiyim; Hayati, Nur; Toyyibah, Nurul; Ningsih, Purnama (Malacca: Journal of Management and Business Development, 2024)
Financing is one that is really needed by the community to meet their needs, one of which is the financing contained in the BMT NU larangan branch, namely congregation-based service financing (LASISMA), this financing uses the Al qordhul Hasan contract and customers or partners increase every year. In this study, researchers describe. How is the implementation of congregation-based service financing (LASISMA) in the larangan subdistrict customer business at the larangan branch of BMT NU, the researcher also describes what are the inhibiting and supporting factors in congregation-based service financing (LASISMA) at the larangan branch of NU BMT. The result of this research is a congregation-based service financing scheme (LASISMA) in increasing business. customers, the BMT groups members of at least 5 and a maximum of 20 members, then BMT provides basic education and conducts surveys, makes letters of recommendation and monitors the customer's business. Factors that become obstacles and supports in financing LASISMA are the existence of groups that also offer similar financing to LASISMA, namely in the form of groups, and also the customer's lack of understanding in managing their business. And one of the supporting factors is the ease of getting financing and installments.